2020
DOI: 10.1002/mar.21339
|View full text |Cite
|
Sign up to set email alerts
|

Not so social: When social media increases perceptions of exclusions and negatively affects attitudes toward content

Abstract: Social media interactions in the form of likes and comments have become a prevalent and expected form of feedback among consumers. However, as these forms of feedback represent social acceptance, content that fails to garner sufficient community reactions may have important implications for consumer behavior, a conjecture supported by an evolutionary psychology account. Three studies demonstrate that consumers use social media cues such as the number of likes that a post receives to shape their attitudes and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 96 publications
0
37
0
Order By: Relevance
“…In light of a social influence perspective (Mittal et al, 2008), further research could consider the effect of social media feedback mechanisms, such as the number of likes (Sundar, 2008), the number and valence of comments (Vinuales & Thomas, 2020), or the number of shares that a misinformation post receives. Finally, as spreading misinformation is a widespread problem across other social media platforms, such as Twitter (Grinberg et al, 2019), future research should confirm the effect of source primacy across different social media contexts and platforms.…”
Section: Limitations and Future Directions For Researchmentioning
confidence: 99%
“…In light of a social influence perspective (Mittal et al, 2008), further research could consider the effect of social media feedback mechanisms, such as the number of likes (Sundar, 2008), the number and valence of comments (Vinuales & Thomas, 2020), or the number of shares that a misinformation post receives. Finally, as spreading misinformation is a widespread problem across other social media platforms, such as Twitter (Grinberg et al, 2019), future research should confirm the effect of source primacy across different social media contexts and platforms.…”
Section: Limitations and Future Directions For Researchmentioning
confidence: 99%
“…Next, Vinuales and Thomas (2021) focus on the affiliative aspects by testing whether certain social media posts that lack a form of social acceptance and hence can be thought of as failing to attract sufficient community reactions (e.g., posts with fewer likes) may increase individuals' perceptions of social exclusion, leading to more negative attitudes toward the branded content featured in the posts, lower purchase intentions, and reduced interest in the brand.…”
Section: Attraction Affiliation and Altruistic Actionsmentioning
confidence: 99%
“…test whether men's proenvironmental consumption acts as an honest signal of altruism, commitment as a partner and father, and mate value in short-and long-term mating contexts (for a similar investigation, seePalomo-Vélez et al, 2020).Next,Vinuales and Thomas (2021) focus on the affiliative aspects by testing whether certain social media posts that lack a form of social acceptance and hence can be thought of as failing to attract sufficient community reactions (e.g., posts with fewer likes) may increase individuals' perceptions of social exclusion, leading to more negative attitudes toward the branded content featured in the posts, lower purchase intentions, and reduced interest in the brand Maldoy et al (2021). examine how the presence of others can make healthy foods appear more appealing.…”
mentioning
confidence: 99%
“…All of these actions are visible to both parties' networks and may possibly induce other members within either network to respond to the original post (Zadeh and Sharda 2014). While insights into specific factors that influence post popularity lack rigor and are relatively sparse (De Vries, Gensler, and Leeflang 2012), there is agreement that the performance of an online post on a social media platform has an effect on the user (Vinuales and Thomas 2021). Vinuales and Thomas (2021) identified that the number of responses received, or the social media performance, is able to shape the users attitudes and intentions regarding the subject of the post.…”
Section: User-generated Contentmentioning
confidence: 99%
“…When a social media user has thoughtfully curated content that aligns to the construction of their identity, which they then share with their online community, they hold an initial expectation of the performance of the content, whether in terms of likes, comments, reactions or sharing of the content. The feedback that users receive on their content, in whichever format, helps users evaluate their "success," or lack thereof (Carr, Hayes, and Sumner 2018, 142;Vinuales and Thomas 2021). However, the use of likes, comments and other feedback mechanisms on social media remains underexplored in the literature (Hayes, Carr, and Wohn 2016;Carr, Hayes, and Sumner 2018).…”
Section: Introductionmentioning
confidence: 99%